From crisis to crisis: individual and organisational empowerment at a university for the third age in Lebanon - Hugo-Henrik Hachem (Zeitschrift für Weiterbildungsforschung - Report)
Abstract In the context of the University for Seniors (UfS) in crisis-hit Lebanon, this paper analysed interview transcripts with 11 older learners (participants) and 12 term-curricula (2018–2024) to answer two research questions: (1) How empowered were older learners to understand the underlying causes of and act facing crisis? Moreover, (2) how did the UfS respond to the crisis as an empowering organisation? Results indicate unmistakable signs of interactional and behavioural empowerment among participants, who also exhibited instances of disempowerment. Post-crisis, UfS moved online, opted for a hybrid modality, and augmented the share of disjuncture-oriented course offerings to help learners address their new social realities. Hence, UfS acted above and beyond an often-critiqued liberal humanist mission and mustered the know-how to deal with recurrent crises. These results are subsequently discussed from the vantage point of four different angles.